Penggunaan Pronomina Persona Pertama \"Kita\" dan Persona Kedua \"Ngana\" Pada Bahasa Melayu Manado Sebagai Penanda Keakraban Bagi Penutur Orang Gorontalo - Bay, Indri Wirabmi (Jurnal Pelangi Ilmu, 2009)
Melayu Manado is one of some languages that are spoken by Gorontalo people. In fact, there are some different things in Melayu manado that are spoken by Manadonese and Gorontalese. The prime difference showed by those things are the employing of first personal pronoun kita and second personal pronoun ngana. This writing aims to describe the using of first personal pronoun kita and second personal pronoun ngana in Melayu Manado Dialect that are spoken by Gorontalese as impolite marker. It will be classified into two points, they are referring to age and kinship. Age entails oldman and oldman, oldman and younger, young man and young man (peer), young man and child. Kinship is related to husband and wife, parent and their children, brother and sister, relative.